How We Lost the Women in Computing. - Vardi, Moshe Y. (Communications of the ACM, 2018)
The article discusses factors creating gender disparity through the underrepresentation of women in computing. Topics include a memo written by engineer James Damore of the search engine firm Google Inc., the historical role of women in computing and code breaking, and problems harming the recruitment of women by Silicon Valley, California technology firms.